2005
DOI: 10.1016/j.ejcts.2005.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The RACHS-1 risk categories reflect mortality and length of stay in a Danish population of children operated for congenital heart disease☆

Abstract: The RACHS-1 classification can also be used to predict in-hospital mortality and length of stay in the Intensive Care Unit in a small volume centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 12 publications
5
55
2
Order By: Relevance
“…The patient's age and weight were not linked to successful fast tracking; however, these are currently the selection criteria used for entry into the fasttrack programme, with exclusion of smaller infants. As reported elsewhere [12,13], there was some indication of variation in hospital stay based on operative procedure, but the small difference observed of less than 1 day between groups was not considered clinically important in this series. The overall length of hospital stay significantly reduced since the programme began in 2006.…”
Section: Discussionsupporting
confidence: 59%
“…The patient's age and weight were not linked to successful fast tracking; however, these are currently the selection criteria used for entry into the fasttrack programme, with exclusion of smaller infants. As reported elsewhere [12,13], there was some indication of variation in hospital stay based on operative procedure, but the small difference observed of less than 1 day between groups was not considered clinically important in this series. The overall length of hospital stay significantly reduced since the programme began in 2006.…”
Section: Discussionsupporting
confidence: 59%
“…The key findings were that the mean weight for age for the PICU was significantly lower than the UK population mean; that patients with highest and lowest categories of weight for age (difference between the child's weight and the UK mean for age is more than 3.5 standard deviations) had the highest mortality; and the patients in the mild to moderately overweight for age category had the lowest mortality. This finding is in keeping with previous paediatric data from Australia [10] (where Numa et al also reported a ''U-shaped'' mortality curve when related to weight for age centiles); from the USA [11] where obesity was not associated with increased mortality or morbidity and from Denmark where low weight was a predictor of mortality following cardiac surgery [12].…”
supporting
confidence: 90%
“…It was even higher than in prior reports. 4,12,14 Risk adjustment is important to accurately compare in-hospital mortality. 4,15 This method would be useful for similar programs in the developing world.…”
Section: Discussionmentioning
confidence: 99%